2022
DOI: 10.1007/s00415-022-11400-8
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic space is age-dependent

Abstract: Knowledge of the physiological endolymphatic space (ELS) is necessary to estimate endolymphatic hydrops (ELH) in patients with vestibulocochlear syndromes. Therefore, the current study investigated age-dependent changes in the ELS of participants with normal vestibulocochlear testing. Sixty-four ears of 32 participants with normal vestibulocochlear testing aged between 21 and 75 years (45.8 ± 17.2 years, 20 females, 30 right-handed, two left-handed) were examined by intravenous delayed gadolinium-enhanced magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
0
1
Order By: Relevance
“…In the same regression model, patient age did not significantly affect the presence of ELH. Dieterich et al (18) recently reported that the size of the endolymphatic space on MRI correlated positively with age (21–75 yr) in 32 healthy subjects with normal vestibular function. Conversely, Inui et al (19) reported that the size of the endolymphatic space in 24 healthy control subjects was smaller in older (>60 yr) individuals than in younger (<60 yr) individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In the same regression model, patient age did not significantly affect the presence of ELH. Dieterich et al (18) recently reported that the size of the endolymphatic space on MRI correlated positively with age (21–75 yr) in 32 healthy subjects with normal vestibular function. Conversely, Inui et al (19) reported that the size of the endolymphatic space in 24 healthy control subjects was smaller in older (>60 yr) individuals than in younger (<60 yr) individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Распространенность развития двусторонней формы заболевания увеличивается с возрастом [17]. Общая частота пациентов с двусторонней формой БМ -24%, из которых у 11% двусторонняя форма заболевания устанавливалась уже при первых признаках БМ, а у 14% заболевание прогрессировало от односторонней к двусторонней форме [18]. По некоторым данным, односторонняя форма БМ прогрессировала до двусторонней формы у 35% пациентов в течение 10 лет и у 47% в течение 20 лет [19].…”
Section: эпидемиологияunclassified